Effect of palm kernel cake as protein source in a concentrate diet on intake, digestibility and live weight gain of goats fed napier grass - Abdullah, Ramli; Rahman, M.M.; Wan Embong, W.K.; Nakagawa, T.; Akashi, R. (2013)
The effects of palm kernel cake (PKC) as a protein source in a concentrate diet (comprising 35 % crushed maize, 30 % rice bran, 32 % PKC, 2 % vitamin mineral premix and 1 % salt) were examined on intake, live weight (LW) gain and digestibility in female goats (average LW of 12. 4 ± 2. 6 kg). Four goats were randomly allocated to each of the four treatment diets: (a) Napier grass (Pennisetum purpureum) offered ad libitum (T1), (b) T1 + concentrate at 0. 5 % of LW (T2), (c) T1 + concentrate at 1. 0 % of LW (T3) and (d) T1 + concentrate at 2. 0 % of LW (T4). A 7-day digestibility trial and an 82-day growth experiment were conducted. No differences were observed among diets for intakes of roughage dry matter (DM), total DM, organic matter (OM) and neutral detergent fibre (NDF). The crude protein (CP) intake increased (P < 0. 05) as the level of concentrate in the diets increased. Goats fed the T2, T3 and T4 diets gained 10. 2, 34. 1 and 52. 5 g/head/day, respectively, while the control group (T1) lost weight (-12. 7 g/head/day). The apparent digestibilities of DM, OM and CP were similar (P > 0. 05) among treatments. The digestibility of dietary NDF decreased (P < 0. 05) with increasing levels of concentrate, but there was no significant (P > 0. 05) difference between T2 and T3 diets. Supplementing a basal diet of Napier grass with PKC-based concentrate improved CP intake and LW gain. The PKC-based concentrate diet can therefore be exploited for the use of local feed resources for goat production; however, further research is required to achieve the best growth response. © 2012 Springer Science+Business Media Dordrecht.